Total Wrist Replacement: A Retrospective Comparative Study - Cooney, William; Manuel, Jennifer; Froelich, John; Rizzo, Marco (Journal of Wrist Surgery, 2012)
Purpose Total wrist arthroplasty (TWA) is an evolving procedure for the treatment of arthritis of the wrist joint. The purpose of this study is to compare outcomes of three different total wrist implants.Methods A retrospective review of the Biaxial, Universal 2, and Re-Motion total wrist arthroplasties was performed. Patients were evaluated for clinical outcome, radiographic analysis, review of complications (incidence and type), and conversion to wrist fusion. Patient function measures included: the Mayo wrist score, the Patient Related Wrist Evaluation, and Disabilities of Arm, Shoulder, and Hand (DASH) score.Results Forty-six wrist implants were performed in 39 patients. There were 36 rheumatoid and 10 posttraumatic cases. The average follow-up was 6 years (3.5 to 15). The total wrist inserted included 16 resectional arthroplasties (Biaxial) and 30 resurfacing designs (Universal 2 and Re-Motion). Nine implant failures were noted. Causes for arthroplasty failure included distal component implant loosening and wrist instability. Salvage procedures included revision TWA or wrist fusion. In successful cases, flexion and extension motion averaged 30 and 38 degrees, respectively, and grip strength improved by 3 kg. Mayo wrist scores, in successful cases, increased from 40 (preoperative) to 76 (postoperative). The Mayo wrist scores for posttraumatic conditions averaged 87 points versus 71 points for rheumatoid arthritis. The average DASH score for the two resurfacing designs were 20 and 37, and 48 for the resectional arthroplasty design.Discussion Total wrist replacement maintains itself and provides good pain relief and functional motion in over 80% of all cases and in 97% of resurfacing implants. Better results were correlated with improved distal component fixation and minimal resection of the distal radius.Level of Evidence Level 3 Case Control
Keywords: arthroplasty; rheumatoid; total wrist; joint